Human Impact on the Environment An Illustrated World Atlas - Govorushko, Sergey (Springer International Publishing : Imprint: Springer, 2016)
This atlas presents a collection of geographical maps showing human impact on the environment. A wide variety of human impacts are discussed, ranging from the energy, mining, transport and agricultural industries as well as less visible impacts such as those of space exploration. This book is a highly illustrated atlas with more than 300 photos from more than 60 countries. Each map is accompanied by a short description of each human impact and its effect on the specific natural environment.